1991
DOI: 10.1192/bjp.159.1.106
|View full text |Cite
|
Sign up to set email alerts
|

Personality as a Vulnerability Factor to Depression

Abstract: One hundred and forty non-depressed primiparous women in a stable relationship completed two personality measures (the EPI and the IPSM) antenatally, and were then assessed for depression at several times post-natally. The risk of depression at six months was increased up to tenfold by high interpersonal sensitivity and threefold by high neuroticism. When previously depressed women were excluded from analyses, high interpersonal sensitivity and, to a lesser extent, high neuroticism were still associated with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
183
2
4

Year Published

1993
1993
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 324 publications
(209 citation statements)
references
References 38 publications
17
183
2
4
Order By: Relevance
“…Personality traits appear to have a considerable heredity component 68 and it has been suggested that a certain type of personality or temperament represents a risk factor for developing major depression. 69,70 Depression has been associated with higher scores on neuroticism (N) and the temperament dimension harm avoidance (HA), the tendency to respond to signals of adverse stimuli with behavioral inhibition. [70][71][72][73][74][75][76][77][78] Also, low self-directedness (the ability to regulate one's behavior and commit to chosen goals; SD) and cooperativeness (the ability to identify with and accept other people; C) have been found in depressed patients, 77,79 which may increase after treatment.…”
Section: Personalitymentioning
confidence: 99%
“…Personality traits appear to have a considerable heredity component 68 and it has been suggested that a certain type of personality or temperament represents a risk factor for developing major depression. 69,70 Depression has been associated with higher scores on neuroticism (N) and the temperament dimension harm avoidance (HA), the tendency to respond to signals of adverse stimuli with behavioral inhibition. [70][71][72][73][74][75][76][77][78] Also, low self-directedness (the ability to regulate one's behavior and commit to chosen goals; SD) and cooperativeness (the ability to identify with and accept other people; C) have been found in depressed patients, 77,79 which may increase after treatment.…”
Section: Personalitymentioning
confidence: 99%
“…Its importance as a psychological construct is further enhanced by its well documented correlation with common psychiatric disorders, that is, high levels of neuroticism predict the onset and subsequent episodes of major depression [2][3][4][5] and are associated with symptoms of depression and anxiety in the general population. [6][7][8][9] The correlation between anxiety, major depression and neuroticism is, in part, due to the presence of shared genetic factors, [10][11][12][13] an observation that has spurred attempts to map the genetic basis of neuroticism.…”
Section: Introductionmentioning
confidence: 99%
“…Two metaanalyses have concluded that presence of the short variant of this repeat (5-HTT-linked polymorphic region, 5-HTTLPR) is associated with higher levels of neuroticism or harm avoidance (5,6). Although neuroticism itself is a risk factor for depression (7), the link between 5-HTTLPR genotype and depression has been more tenuous, suggesting that 5-HTTLPR genotype does not have a consistent main effect on depression but instead may be moderated through other variables (8).…”
mentioning
confidence: 99%